Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004660
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section for non-medical reasons at term

Abstract: Data collection and analysis We identified no studies that met the inclusion criteria. Main results There were no included trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 44 publications
1
50
0
1
Order By: Relevance
“…The truth is that there is currently insuffi cient data [73] and no evidence from randomised controlled trials (RCTs) upon which to base any practice recommendations regarding CDMR [53] . In the absence of studies on CDMR, the knowledge base rests chiefl y on indirect evidence from proxies posing unique and signifi cant limitations [109] .…”
Section: Interpretation Of Recent Evidencementioning
confidence: 99%
“…The truth is that there is currently insuffi cient data [73] and no evidence from randomised controlled trials (RCTs) upon which to base any practice recommendations regarding CDMR [53] . In the absence of studies on CDMR, the knowledge base rests chiefl y on indirect evidence from proxies posing unique and signifi cant limitations [109] .…”
Section: Interpretation Of Recent Evidencementioning
confidence: 99%
“…A commitment to women's right to choose and their right to act on their choice supported by government and maternity care professionals is paramount.-Women's perceptions about the safety of a CS, compared to Vaginal Birth After Caesarean (VBAC) for mother and baby could indicate the type of information they have accessed and therefore their knowledge regarding birth options after CS and the impact of this on subsequent decision making. CS is a life saving intervention in certain circumstances, 23 but it must be recognized as a major surgical procedure with potential adverse effects on both mother and baby. 10 Many women choose CS to reduce the risk to their baby, yet there is a correlation between the CS rate and negative maternal and neonatal health outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…15 Thompson reviewed qualitative literature, but searched limited databases and only included studies from high-income countries. 9 Lavender et al 16 assessed evidence from randomized controlled trials; however, in the absence of data, they concluded there is "an urgent need for a systematic review and synthesis of qualitative data. "…”
mentioning
confidence: 99%